2012
DOI: 10.1021/cn3000026
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analysis of Axonal Transport by Using Compartmentalized and Surface Micropatterned Culture of Neurons

Abstract: Mitochondria, synaptic vesicles, and other cytoplasmic constituents have to travel long distance along the axons from cell bodies to nerve terminals. Interruption of this axonal transport may contribute to many neurodegenerative diseases including Alzheimer's disease (AD). It has been recently shown that exposure of cultured neurons to β-amyloid (Aβ) resulted in severe impairment of mitochondrial transport. This Letter describes an integrated microfluidic platform that establishes surface patterned and compart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…Because the sorting of proteins to lysosomes is ubiquitin-dependent (73), it suggests that by altering ubiquitin homeostasis, A␤ can trigger lysosome dysfunction and the observed transport deficits. Furthermore, we and others have found that A␤ directly affects mitochondrial transport and may be due to defective fission/fusion (58,75), which is regulated by ubiquitination (76). Thus, it suggests that ubiquitination/deubiquitination plays a vital role in regulating axonal transport.…”
Section: Discussionmentioning
confidence: 73%
“…Because the sorting of proteins to lysosomes is ubiquitin-dependent (73), it suggests that by altering ubiquitin homeostasis, A␤ can trigger lysosome dysfunction and the observed transport deficits. Furthermore, we and others have found that A␤ directly affects mitochondrial transport and may be due to defective fission/fusion (58,75), which is regulated by ubiquitination (76). Thus, it suggests that ubiquitination/deubiquitination plays a vital role in regulating axonal transport.…”
Section: Discussionmentioning
confidence: 73%
“…Research indicates that mitochondrial movement is significantly impaired following neuronal injuries, such as glutamate excitotoxicity and zinc neurotoxicity, which led to some effects observed in ischemia. 56 The microgroove component of the microfluidic device could permit facile quantification of retrograde and anterograde trafficking of mitochondria along neuron processes, 57, 58 making the device an ideal system to explore relationships between axonal degeneration and mitochondrial dysfunction in neurons cultured alone or in the presence of other cells.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the ability to direct axonal growth and to precisely control the microenvironments of axons offers a new tool to overcome several limitations in answering multiple aspects of axonal biology that have been previously hindered by a lack of appropriate in vitro cell culture platform. Adaptations of the compartmentalized design have been utilized to investigate biochemical sensors in hippocampal neurons, [34] isolating axonal mRNA from cortical neurons, [35,36] dendrite-to-nucleus signaling, [37] presynaptic differentiation, [38] netrin-dependent axon guidance, [39] distal projections of human embryonic stem cells, [40] axonal diodes, [41] functional imaging of neuron-astrocyte interactions, [42] quantitative analysis of axonal transport, [43] co-culture of neurons and glia cells, [44,45] and neuronal activities on microelectrode arrays. [4648] …”
Section: Recapitulating the Human Brain Pathophysiologymentioning
confidence: 99%